2005
DOI: 10.1063/1.2137455
|View full text |Cite
|
Sign up to set email alerts
|

Fe – Ga ∕ Pb ( Mg 1 ∕ 3 Nb 2 ∕ 3 ) O 3 – Pb Ti O 3 magnetoelectric laminate composites

Abstract: We have found large magnetoelectric (ME) effects in long-type laminate composites of Fe–20%Ga magnetostrictive alloys and piezoelectric Pb(Mg1∕3Nb2∕3)O3–PbTiO3 single crystals. At lower frequencies, the ME voltage coefficient of a laminate with longitudinally magnetized and longitudinally polarized (i.e., L-L mode) layers was 1.41V∕Oe (or 1.01V∕cmOe). Near the natural resonant frequency (∼91kHz) of the laminate, the ME voltage coefficients were found to be dramatically increased to 50.7V∕Oe (36.2V∕cmOe) for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] It has been seen that the strongest ME coupling is often achieved not with single phase materials, but using strain-mediated ME composite systems of magnetostrictive and piezoelectric layers, 11 which have been designed to generate giant ME coefficients. [6][7][8][9][10] Under magnetic field, strain generated by a magnetostrictive layer is transmitted to a piezoelectric layer resulting in a change in electric polarization. Accordingly, a magnetic signal is converted into an induced voltage that can be utilized to sense and measure magnetic fields.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10] It has been seen that the strongest ME coupling is often achieved not with single phase materials, but using strain-mediated ME composite systems of magnetostrictive and piezoelectric layers, 11 which have been designed to generate giant ME coefficients. [6][7][8][9][10] Under magnetic field, strain generated by a magnetostrictive layer is transmitted to a piezoelectric layer resulting in a change in electric polarization. Accordingly, a magnetic signal is converted into an induced voltage that can be utilized to sense and measure magnetic fields.…”
mentioning
confidence: 99%
“…One way to increase resolution and reduce the impact of magnetic and environmental noise is to operate at the electromechanical resonance (EMR), thus enhancing a ME . 7,14 Investigations have shown that a ME may be enhanced by up to two orders of magnitude at EMR. 15 However, the advantages of driving the sensor at resonance are only available over a narrow bandwidth.…”
mentioning
confidence: 99%
“…Magnetoelectric ͑ME͒ effects have been studied in homogeneous systems such as single phase ceramics, 1 crystals, 2,3 and eptiaxial crystalline layers; 4 and in inhomogeneous systems such as composites of piezoelectric and magnetostrictive particles 5 and/or laminated layers. [6][7][8][9][10][11][12][13][14][15][16] Composites of piezoelectric Pb͑Zr 1−x Ti x ͒O 3 ͓i.e., ͑PZT͔͒ ceramic or Pb͑Mg 1/3 Nb 2/3 ͒O 3 -x % PbTiO 3 ͑PMN-PT͒ single crystal layers laminated together with Terfenol-D, 8,9 NiFe 2 O 4 , 10,11 Permendur, 12 or Fe-Ga ͑Ref. 13͒ layers have been reported.…”
mentioning
confidence: 99%
“…[5][6][7][8][9] The ME output is increased by one to two orders of magnitude if the structures are driven in mechanical resonance, and the resonance frequency was in the range from tens to hundreds of kilohertz. 9,12 Although giant coupling was reported in terfenol-D based ME composites, the dc biasing magnetic field was relatively high, of the order of 400 500 Oe. Hence, a material with saturation magnetostriction in low applied dc magnetic fields is sought after for applications, as such a composite can deliver high ME outputs at low dc applied magnetic fields, which makes them cost effective and light.…”
Section: Introductionmentioning
confidence: 99%